1992
DOI: 10.2172/10159247
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms governing the direct removal of wastes from the Waste Isolation Pilot Plant repository caused by exploratory drilling

Abstract: Two processes are identified that can influence the quantity of wastes brought to the ground surface when a waste disposal room of the Waste Isolation Pilot Plant is inadvertently penetrated by an exploratory borehole. The first mechanism is due to the erosion of the borehole wall adjacent to the waste caused by the flowing drilling fluid (mud); a quantitative computational model based upon the flow characteristics of the drilling fluid (laminar or turbulent) and other drilling parameters is developed and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Concurrent with the 1992 PA (but not part of the 1992 PA), the quantity of waste particulate released through the spalling of the borehole wall was estimated, i.e., waste released due to the movement of high-pressure gas generated from degradation of containers and organic material to the borehole when the repository was penetrated (Berglund, 1992). Several types of calculations were made and an experimental program was begun to more thoroughly understand the phenomenon.…”
Section: Direct Cutting and Brine Release Modelingmentioning
confidence: 99%
“…Concurrent with the 1992 PA (but not part of the 1992 PA), the quantity of waste particulate released through the spalling of the borehole wall was estimated, i.e., waste released due to the movement of high-pressure gas generated from degradation of containers and organic material to the borehole when the repository was penetrated (Berglund, 1992). Several types of calculations were made and an experimental program was begun to more thoroughly understand the phenomenon.…”
Section: Direct Cutting and Brine Release Modelingmentioning
confidence: 99%
“…The value of the shear stress acting on the borehole wall can then be determined from Equation (8). Using an iterative procedure similar to that for the laminar flow problem, the fluid shear stress can be forced to equal the repository shear resistance to erosion (zfaa) to obtain the final eroded borehole radius (Berglund, 1992).…”
Section: (08165) 'mentioning
confidence: 99%
“…The calculations performed by Berglund(1992) and preliminary results from 1D experiments conducted in late 1993 and early 1994 (Berglund and Lenke 1994) on gas pressurized porous granular media have indicated that if a drillbit inadvertently penetrates a gas pressurized WIPP disposal room, failure (spall) of the waste adjacent to the drillbit can occur followed by the compression of the waste against the drillstring surface. The compressed waste is likely to cause either sticking of the drillstring assembly or to exacerbate erosion adjacent to the drillpipe and consequently cause a quantity of waste to reach the ground surface.…”
Section: Constructedmentioning
confidence: 99%
See 2 more Smart Citations